2023
DOI: 10.1093/gbe/evad211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Widely Used Phylogenetic Models for Gene Expression Evolution

Jose Rafael Dimayacyac,
Shanyun Wu,
Daohan Jiang
et al.

Abstract: Phylogenetic comparative methods are increasingly used to test hypotheses about the evolutionary processes that drive divergence in gene expression among species. However, it is unknown whether the distributional assumptions of phylogenetic models designed for quantitative phenotypic traits are realistic for expression data and importantly, the reliability of conclusions of phylogenetic comparative studies of gene expression may depend on whether the data is well described by the chosen model. To evaluate this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…other studies have shown expression counts for many genes in this dataset (and many others) are not welldescribed by a Brownian process [66,131]. As such, some of their observed correlations could be spurious due to unmodeled phylogenetic structure [35].…”
Section: A Case Study Of Including Eigenvectors As Covariates In Pglsmentioning
confidence: 73%
“…other studies have shown expression counts for many genes in this dataset (and many others) are not welldescribed by a Brownian process [66,131]. As such, some of their observed correlations could be spurious due to unmodeled phylogenetic structure [35].…”
Section: A Case Study Of Including Eigenvectors As Covariates In Pglsmentioning
confidence: 73%
“…For example, many studies either assume a single species-level phylogeny that has been estimated using coalescent-based (Doña and Johnson, 2023) or traditional concatenation approaches (Hensen et al 2023), or a single gene tree (e.g., Ross et al 2004; Al-Kahtani et al 2004; Kamilar and Cooper 2013; Adams et al 2014; Gu 2016; Dunn et al 2018; Chen et al 2023) to model trait evolution. However, this assumption may (Dimayacyac et al 2023) or may not (Hahn and Nakhleh 2016a) be the best strategy. On the other hand, modeling evolution as a function of a particular gene tree may prove beneficial for traits predicted to exhibit a more direct one-to-one correspondence with a single tree, such as expression of a gene largely regulated by cis elements near its encoded locus (Chen et al 2019; Bertram et al 2022; Bastide et al 2023; Dimayacyac et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption may (Dimayacyac et al 2023) or may not (Hahn and Nakhleh 2016a) be the best strategy. On the other hand, modeling evolution as a function of a particular gene tree may prove beneficial for traits predicted to exhibit a more direct one-to-one correspondence with a single tree, such as expression of a gene largely regulated by cis elements near its encoded locus (Chen et al 2019; Bertram et al 2022; Bastide et al 2023; Dimayacyac et al 2023). Perhaps such scenarios arguably represent a best case in which we might at least hope to match tree with trait.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations